A cross-cultural study of the construct of Forgiveness: Britain, Greece and Cyprus - E. W. Scobie, Geoffrey; D. Scobie, Enid; K. Kakavoulis, Alexandros (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF